HOSPITALITY MEETS AESTHETICS : INTERIOR DESIGN OF HOTEL LOBBIES IN RELATION TO TOURISM (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
In the tourism industry, architecture and interior design are more than functional backdrops they act as catalysts for experience. Among hotel spaces, the lobby holds unique importance as it forms the “first impression” for guests and sets the tone for their stay. Contemporary hospitality design increasingly recognizes the lobby as a multifunctional cultural and experiential space, where aesthetics, branding, and guest comfort intersect. The hotel lobby is a crucial space that establishes the first impression for guests, shaping their overall perception of hospitality and influencing tourism experiences. This article examines the role of hotel lobby interior design in tourism, focusing on how spatial arrangement, materials, lighting, and cultural identity enhance guest satisfaction and destination branding. By analyzing exemplary hotel lobby designs, the study highlights the intersection of aesthetics, functionality, and cultural repres The hotel lobby is the first point of contact between guests and the hospitality environment, making it a vital element in shaping perceptions and tourism experiences. This article examines the interior design of the Aureverra Flow hotel lobby, developed with the concept of Sculptural Organic Flow, to illustrate how aesthetics, materiality, and spatial organization contribute to tourism appeal. The lobby integrates natural luxury, cultural symbolism, and functional circulation into a harmonious design that enhances both guest satisfaction and destination branding. Findings show that lobby interiors, when thoughtfully designed, can transform into iconic tourism assets, illustrating how lobbies contribute to both hospitality competitiveness and tourism development.  The research applies a case study approach, analyzing the Aureverra Flow lobby project through spatial diagrams, design drawings, material specifications, and conceptual narratives. The analysis emphasizes how design elements such as space, materials, lighting, and symbolism support tourism experience and hospitality branding.
Keywords: Hotel Lobby; Interior Design; Tourism; Guest Experience; Hospitality Architecture